GROWTH RATES OF ISLAMIC FINANCE: A BIBLIOMETRIC ANALYSIS BASED ON THE NUMBER OF PUBLICATIONS - Nur Iza Faizah; Fidri Fadillah Puspita; Diana Lestari; Indriyeni Indriyeni (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
Islamic Finance, which is related to "Islamic finance", is a form of activity related to money which is financial products and services with Islamic principles. Islamic finance aims to avoid all actions related to bad deeds in accordance with the Koran, such as the term MAGRIB, namely Maysir, Gharar, Riba, Haram and Dzalim. Conventional-based financial services such as banks, insurance, stocks, investments and all those related to their services are the most prominent in society. Thus, this study aims to present the latest trends from Islamic Finance studies. This study uses bibliometric analysis based on data obtained from Scopus. By entering the keywords used, related to Islamic Finance in the title of the article, this study succeeded in obtaining 2028 documents for more detailed analysis. Various applications are used, such as Microsoft Excel to perform frequency analysis, VOSviewer for data visualization. This study presents the results using standard bibliometric analysis such as year of publication, type of document, type of source, title of source, language, subject area, keywords, geographic distribution, authorship and active institution. Based on our results, there has been an extraordinary growth in Islamic finance publications since 2005. The increasing number of articles on Islamic finance shows the importance of Islamic-based finance in the financial services industry